Implementation of STEM Integrated Ethnoscience-based Vocational Science Learning in Fostering Students' Higher Order Thinking Skills (HOTs) - PH, Qori Agussuryani; Sudarmin, Sudarmin; Sumarni, Woro; Subali, Bambang; Saptono, Sigit (International Journal of Active Learning, 2020)
The low HOTs of students is caused by the lack of opportunities to think scientifically. The research objective was to analyze HOTs profiles through Analyze (C4), Evaluate (C5), and Create (C6) indicators through science learning based on integrated ethnoscience STEM (Science, Technology, Engineering, and Mathematics). The research method was a quasi-experimental one-group pretest-posttest design with a purposive sampling technique in Class X SMK Accounting 1 which consisted of 37 students. The data collection method used HOTs test questions with the concept of